Enhanced Performance of a Novel Quaternary Nanocomposite CuO/ZnO/ZnS/CuS towards Removal of Dye Pollutant under Simulated Sunlight Irradiation. Issue 29 (4th August 2020) - Zhu, Wenli; Du, Juan; Yang, Qiaoling; Liu, Dongliang
Abstract: The novel quaternary nanocomposites CuO/ZnO/ZnS/CuS have been successfully synthesized via a green microwave technique using dispersed ZnS micosphere and CuO nanoleaf. More particularly, the sphere‐like ZnS and leaf‐like CuO were mainly responsive to the visible and ultraviolet light, respectively. The quaternary nanocomposites CuO/ZnO/ZnS/CuS were sensitive to both ultraviolet and visible light. When prepared at lower mass ratio of CuO to ZnS, the quaternary nanocomposites showed excellent adsorption capacity in the dark, and remarkable photocatalytic capacity towards Rhodamine B (RhB) dye under the simulated sunlight within a short irradiation time more quickly and efficiently than that of pure CuO and ZnS. The mechanism investigation indicated the photodegradation of RhB dye under the simulated sunlight was mediated by the superoxide radicals and holes. Additionally, the quaternary nanocomposite CuO/ZnO/ZnS/CuS could be easily reused with higher activity. Abstract : Solar light‐driven quaternary nanocomposites CuO/CuS/ZnO/ZnS synthesized at lower mass ratio of CuO to ZnS exhibit higher adsorption and photocatalytic capacity for dye pollutant treatment within a short time. The dye pollutant removed by the heterogeneous catalyst was mediated by superoxide radical.